Zenker’s diverticulum: etiopathogenesis, symptoms and diagnosis. Comparison of operative methods - Nehring, Piotr; Krasnodębski, Ireneusz W. (Gastroenterology Review/Przegląd Gastroenterologiczny, 2013)
Zenker’s diverticulum is an alimentary tract pouch localized in the area of the upper esophageal sphincter. Treatment procedure complications and coexisting diseases constitute a serious diagnostic and therapeutic problem. Characteristic symptoms and signs facilitate differential diagnosis, simultaneously being real patient maladies. There are many treatment procedures leading to pouch septum reduction and decrease of upper esophageal sphincter pressure. After years of experience in operating and endoscopic treatments we found it necessary to compare these different methods.